The Effect of Service Quality, Corporate Image, Customer Trust, Customer Satisfaction, And Customer Experience on Customer Loyalty at PT Pelindo (Persero) (Case Study at Tanjung Intan, Gresik, And Tanjung Perak Port) - Puput Tri Hantoro; Herni Justiana Astuti; Erny Rachmawati; Wida Purwidianti (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the effect of service quality, company image, customer trust, customer satisfaction, and customer experience on customer loyalty at PT Pelindo (Persero). The data collection technique uses a purposive sampling method, where the requirement to be sampled is service users who have used PT Pelindo (Persero) services for 1 year. Based on this technique, a sample of 112 respondents was obtained—data analysis using SEM PLS. The results showed that service quality, company image, customer trust, customer satisfaction, and customer experience positively and significantly affect customer loyalty at PT Pelindo (Persero). This study recommends PT Pelindo (Persero) maintain and continue to improve service quality to maintain service user loyalty to compete with TUKS Ports in Indonesia.